Pengaruh Kompetensi dan Kompensasi terhadap Kinerja Perawat dengan Keterikatan Kerja sebagai Variabel Intervening pada Rumah Sakit Rosela Karawang - Fadila Hanoum Nurifai; Stefanus M. S Sadana (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
High-quality human resources and nursing professionalism are vital for maintaining hospital service standards. This research addresses concerns regarding compensation, work engagement, and turnover risks among healthcare staff. The study specifically evaluates how competency and compensation systems impact nurse performance at Rosela Hospital. Employee engagement is analyzed as a critical intervening variable within this professional healthcare clinical setting. Data were gathered via questionnaires from 96 nurses to assess these organizational and behavioral factors. SmartPLS version 4.0.9.6 served as the primary analytical tool for processing the collected research data. Results indicate that both competency and compensation exert a direct positive effect on nurse performance. Furthermore, employee engagement was found to significantly influence overall productivity and service quality levels. The analysis confirms that engagement mediates the relationship between professional competency and final work outcomes. Better compensation packages are shown to strengthen the emotional and professional commitment of the staff. The findings suggest that integrated management strategies are essential for optimizing nursing performance in Karawang. Enhancing skill sets and rewards leads to higher engagement, which ultimately improves patient care delivery. This study highlights the necessity of supporting nurses to ensure the long-term success of Rosela Hospital.